A CASE STUDY OF THE BEHAVIOR OF SOIL-NAIL SUPPORTED DEEP MIXED WALL IN THE SOFT DEPOSIT OF SHANGHAI - L. Ma; S. L. Shen; Y. J. Du; W. J. Sun (International Association of Lowland Technology, 2011)
This paper presents a case study of an excavation retained by soil-nail supported deep mixed (DM) wall (DMSNW) in soft deposit of Shanghai, China. The soft deposit in Shanghai is Quaternary sediment with silt content over 50% and clay content of about 40%. The strength of this deposit is very low and the sensitivity is very high. In order to retain the excavation in the soft deposit, soil-nail supported DM wall is generally adopted when the excavation depth is less than 6 m. This paper presents an investigation on the interaction mechanism between nail and surrounding soil through a field case. A two-dimension finite element method (2D-FEM) was conducted. The effectiveness of 2DFEM is verified via comparing calculated DM wall displacement with the field measured value. Based on the FEM result, the importance of four key design factors, e.g. nail length, nail spacing, thickness of DM wall, and stiffness of DM wall, are discussed. The results indicate that FEM analysis is an efficient way to predict the displacement and internal force of nails. Finally, a design chart is proposed for the soil-nail supported DM wall used in excavation practice.